The Role of Management Accounting Systems in Improving the Performance of Culinary MSMEs: Moderation of Sustainability Reporting - Ilma Wulansari Hasdiansa (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of management accounting systems on the performance of culinary MSMEs and test the role of sustainability reporting as a moderation variable. The research uses a quantitative approach with a survey method of 100 culinary MSMEs operating in the central area of Makassar City. Data were collected through a questionnaire with a Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results of the study show that the management accounting system does not have a significant effect on business performance. This indicates that most MSMEs still do not make optimal use of accounting information in decision-making. Meanwhile, sustainability reporting has been proven to have a positive and significant influence on business performance. However, sustainability reporting is not able to moderate the relationship between management accounting systems and business performance. These findings show that sustainability practices have a more direct role in improving the performance of MSMEs compared to management accounting systems that have not been implemented effectively. This research contributes to the development of management and sustainability accounting literature, as well as provides practical implications for MSME actors in improving business performance through the integration of information systems and sustainable business practices.